Etika Sufistik Dalam Pemikiran Muhammad Nursamad Kamba - Yuwono, Adhimas Alifian (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2025)
This research aims to explore reflectively the Sufistic ethical thinking of Muhammad Nursamad Kamba as part of the modern Sufism movement where the focus of the study is more emphasised on the social-humanitarian ethical dimension. This type of research is a document study conducted by collecting data from primary sources in the form of Kamba's books, and secondary sources in the form of journals, books, and related website articles. The results of this research are: Sufistic ethics in Kamba's thought begins with the application of the principle of independence in religion by accessing divine values directly without being hindered by religious authorities who give birth to formal laws. After that, Kamba makes the principle of ‘to be god is to do good’ a fundamental foundation in religion. Thus, the tendency towards the moral dimension will be very dominant in the life of a Muslim. That doing good is solely because Allah is the Most Good. There is no sense of selfishness, riya', pride, ujub, and so on. His life is only to nurture fellow creatures of Allah because he sees Allah in other creatures. This style of thinking includes two ethical concepts at once, namely individual ethics in the form of upholding obligations to God, and social ethics in the form of efforts to reflect divine values in the behaviour of kindness and love. Penelitian ini hendak mengeksplorasi secara reflektif pemikiran etika sufistik Muhammad Nursamad Kamba sebagai bagian dari gerakan tasawuf modern dimana fokus kajiannya lebih ditekankan pada dimensi etik sosial-kemanusiaan. Jenis penelitian ini adalah studi dokumen yang dilakukan dengan cara mengumpulkan data dari sumber primer berupa buku karya Kamba, dan sumber sekunder berupa jurnal, buku, dan artikel website terkait. Hasil dari penelitian ini adalah: etika sufistik dalam pemikiran Kamba dimulai dengan penerapan prinsip kemandirian dalam beragama dengan mengakses nilai ketuhanan secara langsung tanpa terhalangi oleh otoritas keagamaan yang melahirkan hukum-hukum formal. Setelah itu, Kamba menjadikan prinsip “bertuhan adalah berbuat baik” sebagai landasan fundamental dalam beragama. Dengan demikian, kecenderungan pada dimensi akhlak akan sangat dominan dalam kehidupan seorang muslim. Bahwa berlaku baik adalah semata-mata karena Allah Yang Maha baik. Tidak ada rasa pamrih, riya’, sombong, ujub, dan sebagainya. Hidupnya hanyalah untuk mengayomi sesama makhluk Allah karena melihat Allah dalam diri makhluk yang lain. Corak pemikiran tersebut mencakup dua konsep etik sekaligus, yaitu etika individual berupa penegakan kewajiban kepada Tuhan, dan etika sosial berupa upaya merefleksikan nilai ketuhanan dalam perilaku kebaikan dan cinta.